Perlindungan Hukum Masyarakat dari Dampak Negatif Penggunaan AI - Maharani, Bondan Ayu; Rahajeng, Hasnaa Amelia; T, Triana; Arianti, Zahra Dwi (Media Hukum Indonesia (MHI), 2025)
the development of artificial intelligence (AI) has made a major contribution to various fields of life, from health, education, to industry. However, this progress also has negative impacts, especially if used unwisely. This study aims to examine legal protection for the public from the negative impacts of the use of AI, especially related to copyright infringement, plagiarism, and misuse of deepfake technology that can be detrimental both personally and socially. Using normative legal research methods and a literature study approach, the results of the study show that although AI provides many benefits, there are significant legal risks, including violations of privacy, intellectual property rights, and defamation. Therefore, comprehensive regulations and awareness of the public and technology developers are needed so that AI is used ethically and responsibly. Strong legal protection must be balanced with an approach that upholds human dignity and human value.